2018
DOI: 10.2516/ogst/2018006
|View full text |Cite
|
Sign up to set email alerts
|

Efficient estimation of hydrolyzed polyacrylamide (HPAM) solution viscosity for enhanced oil recovery process by polymer flooding

Abstract: Abstract. Polymers applications have been progressively increased in sciences and engineering including chemistry, pharmacology science, and chemical and petroleum engineering due to their attractive properties. Amongst the all types of polymers, partially Hydrolyzed Polyacrylamide (HPAM) is one of the widely used polymers especially in chemistry, and chemical and petroleum engineering. Capability of solution viscosity increment of HPAM is the key parameter in its successful applications; thus, the viscosity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 83 publications
0
32
1
Order By: Relevance
“…The bulk of studies have demonstrated that extension of a reliable and robust model is highly in the need of a comprehensive and wide‐ranging databank . Hence more than 140 datapoints of silica solubility in association with pressure and boiler water silica content are taken from the open literature .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of studies have demonstrated that extension of a reliable and robust model is highly in the need of a comprehensive and wide‐ranging databank . Hence more than 140 datapoints of silica solubility in association with pressure and boiler water silica content are taken from the open literature .…”
Section: Resultsmentioning
confidence: 99%
“…The bulk of studies have demonstrated that extension of a reliable and robust model is highly in the need of a comprehensive and wide-ranging databank [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Hence more than…”
Section: Data Preparationmentioning
confidence: 99%
“…The RBF network structure consists of just three layers, which this structure makes the training process of the RBF network easier in comparison with the MLP network [25]. One of the most advantages of RBF networks is that they can be applied to highly noisy data [26]. The function which is applied to the weighting vector of the hidden layer is a non-linear transformation function.…”
Section: Details Of Intelligent Modelmentioning
confidence: 99%
“…As a type of polymers, partially Hydrolyzed Polyacrylamide (HPAM) has been widely used as the main agent of the polymer gel because of its reasonable cost and high efficiency, which is a polyelectrolyte macromolecule with a flexible chain [11][12][13][14][15]. As a type of cross-linkers, the aspiration to use high valence metal ion (Al 3+ or Cr 3+ ), provided in the form of polynuclear olation complex ion (AlCit or Ac 3 Cr), is remarkable due to its economic cost and good adaptability.…”
Section: Introductionmentioning
confidence: 99%